IMPLEMENTASI ALGORITMA GENETIKA DALAM PENJADWALAN KERJA DAN PENGAJUAN CUTI PEGAWAI DI PT.MEDAN SUGAR INDUSTRI - Simbolon, Yolanda Tua Parulian; Gea, Asaziduhu (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2019)
The key to success in achieving the company's vision and mission is not only determined by the availability of technology and the availability of materials owned by the company. However, the potential of human resources is one of the capital that plays an important role in achieving company goals. However, the productivity of human resources can decrease due to various influencing factors. In addition to individual factors that come from the employees themselves, the excessive workload is a factor that can cause a decrease in employee productivity. Therefore, employees need to get good treatment in terms of the division of working hours, so that employees can work more optimally. The division of work shifts is one solution that can be carried out by the company. The problem with the existing leave application system at PT. Medan Sugar Industry is still done manually. Checking the remaining leave, submitting leave, and leaving approval are carried out in stages and still relies on the left card contained in each employee file data. With the Scheduling and Submission System for employee leave using the Genetic Algorithm Method at PT. Medan Sugar Industry, the employee scheduling process can be computerized and more effective.